The Discours Of The Mystical Spinning Through The Symological Perspective - djerrah, wahiba (El Omda in Linguistics and Discourse Analysis, 2024)
This article deals with the analysis; the phenomenon of the use of significance in one of the most famous purposes on which Sufism was adopted in order to express the nature of the relationship that binds them to the eternal reality that they have striven throughout their course to uncover. What are the most important methods on which the Sufis relied upon to build their system? What are the most important features of this symbol? Then, is there a dividing line between the discourse of spinning as a known object since ancient times and its mystical counterpart?